(untitled) (Biological Sciences - PJSIR, 2020)
To evaluate the expression of genes that involved in hypothyroidism by multiple alignment of nucleotide sequences of genes study the functional unit of genes that involve in production of thyroid hormones. The thyroid gland is part of endocrine gland and regulates much vital body function (breathing, heart rate, body weight, body temperature also involve in development, growth, protein production and it also control the central and peripheral nervous system, muscle strength and menstrual cycle). Hypothyroidism is a condition in which thyroid gland does not produce enough thyroid hormone. To find the genetics information than by using bioinformatics tools several genes that were involved in hypothyroidism were identified but six genes TSHR, TPO, THRB, TG, IYD, DUOX2 and their motifs were studied in detail to understand the basic domains involved in this disease.